Positioning justice: a legal cascade of sexual violence cases in Mombasa, Kenya - Olum, Melanie; Githinji, Gerald; Sidi, Abigael; Mokua, Abel; Kiio, Morris; Aliyan, Nawal; Khandwala, Iqbal; Kithinji, Celina; Wanjiku, Saida; Manguro, Griffins; Temmerman, Marleen (Frontiers in Global Women's Health, 2025)
IntroductionSeeking legal redress for sexual violence (SV) is a daunting process for survivors. They must navigate their personal trauma societal stigma, and flawed systems, creating an arduous path to justice. This study was conducted to assess patterns of SV within Mombasa County, Kenya, and details the legal follow-up post-SV care.MethodsA retrospective cross-sectional study was conducted using data from SV survivors attending the Gender-Based Violence and Recovery Centre (GBVRC) at the Coast General Teaching and Referral Hospital (CGTRH) between 2017 and 2023. Data sources include post-rape care (PRC) forms, clinician notes, quarterly reports, police reports, counsellor reports, and paralegal follow-up records. A legal cascade for SV cases was created detailing SV survivors' referral patterns between police and GBVRC attendees who proceeded to court, and judgments rendered.ResultsThe total number of survivors at GBVRC between 2017 and 2023 was 3122; 2738 girls/women and 384 boys/men, with the majority of perpetrators known to the survivors, 2764/3122 (89%). The median age for survivors was 15 years, ranging from less than one year to 63 years with a male median age of 9 and a female median age of 15. Fewer males reported their cases, with 238 out of 384 males (62%) and 2,020 out of 2,738 females (74%). Ninety-three per cent (2906/3122) of cases referred from GBVRC arrived at the police station, though 62% (1864/3022) of these cases were successfully recorded and filed at the police station after follow-up. Additionally, 29% (535/1864) of cases reported did not proceed with investigation. Overall, of the 3022 cases that were referred to and reported, 1746 (57.7%) proceeded to court. Among these, judgments were pronounced in 372 cases (21%) and 85 out of these 372 cases (23%) were either withdrawn or acquitted.DiscussionLack of evidence, poor witness testimonies, or failure of witnesses to present themselves in court were likely causes for withdrawal and acquittal of cases. Sexual violence remains a prevalent concern and should be prioritized as a national agenda. Systems should be strengthened to enhance access to justice while exploring alternatives for legal support, such as paralegal networks that can improve case follow-up.